PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP KUALITAS LABA DIMODERASI DENGAN UKURAN PERUSAHAAN - Rezananda Ramadina; Nurul Hidayah (Universitas Nias Raya, 2025)
This study aims to examine the influence of Good Corporate Governance (GCG) mechanisms on earnings quality in transportation companies listed on the Indonesia Stock Exchange during the 2018–2022 period, with firm size as a moderating variable. GCG is measured using three key indicators: institutional ownership, the proportion of independent commissioners, and the existence of an audit committee. A quantitative approach was employed using secondary data sourced from annual financial reports. Panel data regression analysis was applied, along with Moderated Regression Analysis (MRA) to test the moderating effect. The findings reveal that institutional ownership and audit committees have a significant positive effect on earnings quality, while independent commissioners do not show a significant impact. Moreover, firm size strengthens the relationship between institutional ownership and audit committees with earnings quality but does not moderate the relationship between independent commissioners and earnings quality. These results highlight the importance of effective corporate governance practices and the significant role of firm size in ensuring the credibility of financial reporting.